Unidirectional tough silk fibroin scaffold and preparation method thereof

Through directional freezing and subsequent treatment processes, strong silk fibroin scaffolds with high orientation and crystallinity were prepared, which solved the problem of degradation of mechanical properties of regenerated silk fibroin, and achieved high strength and high biocompatible silk fibroin scaffolds, suitable for tissue engineering applications.

CN119708602AActive Publication Date: 2025-03-28ZHEJIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411761830.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

During the preparation of regenerated silk fibroin, the β-sheet structure of some silk fibroin is destroyed due to chemical treatment steps, resulting in a significant reduction in its mechanical properties, limiting its potential in high-strength applications, especially in tissues that require bearing and tensile stress resistance.

Method used

Through the directional freezing process, strong and highly biocompatible silk fibroin scaffolding with lyophilization, moisture-drying, mechanical compaction and polar solvent-induced β-sheet crystallization were prepared.

Benefits of technology

The tough silk fibroin scaffold with a single orientation structure was prepared, which improved its mechanical properties, and its tensile strength reached 5.12MPa, showing excellent fatigue resistance and biocompatibility, and is suitable for tissue engineering and regenerative medicine research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005167893790000011
    Figure HDA0005167893790000011
  • Figure HDA0005167893790000012
    Figure HDA0005167893790000012
  • Figure HDA0005167893790000021
    Figure HDA0005167893790000021
Patent Text Reader

Abstract

The invention provides a single-oriented tough silk fibroin scaffold and a preparation method thereof. According to the preparation method, the microscopic orientation structure of a fibroin material is regulated and controlled through a directional freezing process, and then the silk fibroin scaffold which is highly oriented, high in crystallinity, biodegradable, tough and high in biocompatibility is prepared in manners of humidification, mechanical compaction and polar solvent induced beta-folding crystallization. The preparation method has the advantages that equipment is simple, operation is easy and convenient, rapid and batch preparation can be achieved, and economic cost is low. The silk fibroin scaffold prepared by the preparation method has the advantages of high orientation, tight interface bonding and high beta-folded crystal content on macroscopic and microscopic levels, and the single-orientation silk fibroin fibers and beta-folded crystals have crack pinning and crack delay effects, so that the toughness of the silk fibroin scaffold can be effectively improved; the unidirectionally-oriented tough silk fibroin scaffold prepared by the method can be applied to tissue engineering and regenerative medicine research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tissue engineering and biomaterial manufacturing under biomedical engineering, and specifically relates to a single-oriented strong and tough silk fibroin scaffold and a preparation method thereof. Background Art

[0002] Silk fibroin is a natural high molecular weight fibrous protein extracted from silk. It is rich in glycine, alanine and serine and has a β-folded structure. These characteristics give silk fibroin excellent biocompatibility and mechanical properties. After dissolution, filtration, dialysis, centrifugation and freeze-drying, water-soluble regenerated silk fibroin can be obtained. Regenerated silk fibroin can be further processed into various forms such as films, sponges, microspheres, gels, nanofibers, etc., and is suitable for a wider range of biomedical and engineering materials.

[0003] However, during the preparation of regenerated silk, due to a series of chemical treatment steps such as dissolution and dialysis, the molecular structure of some silk proteins, especially its β-folding structure, is destroyed, resulting in a significant decrease in the mechanical properties of regenerated silk. This decrease in mechanical properties limits the potential of regenerated silk in certain high-strength applications, especially in tissues that involve load-bearing and tensile stress resistance, such as soft tissues of the locomotor system such as muscles, tendons and ligaments. These soft tissues usually need to withstand tensile stress in a single direction, so their fiber structures mostly present a highly ordered single orientation, which can not only enhance mechanical properties, but also improve the efficiency of stress transfer.

[0004] Therefore, how to construct a tissue engineering scaffold with a single orientation structure and excellent mechanical properties to meet the structural and functional requirements of tissue regeneration such as muscle and tendon is a major challenge facing current research. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a single-oriented strong and tough silk fibroin scaffold and a preparation method thereof, which has the advantages of simple equipment, simple operation, rapid and batch preparation and low economic cost. A highly oriented, highly crystallinity and anisotropic, high-toughness and high-biocompatibility silk fibroin scaffold is prepared.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a unidirectional strong and tough silk fibroin scaffold, which regulates the microscopic orientation structure of the silk fibroin material through a directional freezing process, then removes ice crystals through freeze-drying, and then undergoes humidification, mechanical compaction and polar solvent-induced β-folding crystallization to prepare a highly oriented, highly crystalline and biodegradable strong and highly biocompatible silk fibroin scaffold.

[0008] Specifically,

[0009] A method for preparing a unidirectional strong silk fibroin scaffold comprises the following steps:

[0010] (1) Directionally freezing the silk fibroin aqueous solution to prepare ice crystal / silk fibroin scaffolds;

[0011] (2) freeze-drying the ice crystal / silk scaffold to remove the ice crystals and obtain a directional porous silk scaffold;

[0012] (3) sequentially subjecting the oriented porous silk scaffold to humidification and mechanical compaction treatments;

[0013] (4) Immersing the compacted silk fibroin scaffold in a polar solvent for cross-linking, and washing with water after immersion to obtain the unidirectional strong silk fibroin scaffold.

[0014] In the above step (1):

[0015] Preferably, the silk fibroin aqueous solution is obtained by the following method:

[0016] The water-soluble silk fibroin is put into deionized water and dissolved by magnetic stirring, and then filtered and centrifuged to remove bubbles to obtain a silk fibroin aqueous solution.

[0017] The purpose of filtering the silk fibroin solution is to filter out the undissolved silk fibroin therein to prevent it from affecting the subsequent directional freezing process.

[0018] As a further preferred embodiment, during the centrifugal debubbling, the centrifugal speed is 1000 r / min and the centrifugal time is 5 min. The purpose of the centrifugal debubbling is to prevent bubbles from affecting the subsequent directional freezing process.

[0019] The water-soluble silk fibroin source includes but is not limited to Bombyx mori silk, Tussah silk and spider silk. The water-soluble silk fibroin is preferably derived from Bombyx mori silk.

[0020] Preferably, the concentration of the silk fibroin aqueous solution is 1 to 50 wt %, more preferably 4 to 20 wt %, and even more preferably 4 wt %.

[0021] Preferably, the specific process of directional freezing the silk fibroin aqueous solution is as follows:

[0022] The mold with upper and lower openings is placed on a cold source with a temperature control device (only the bottom of the mold is in contact with the cold source), the silk fibroin aqueous solution is poured into the mold, and the cold source is controlled to cool the silk fibroin aqueous solution until the silk fibroin aqueous solution is completely frozen, thereby completing directional freezing;

[0023] The initial temperature of the cold source is set to 20 to -120°C, the cooling rate is 0 to 20°C / min, and the final temperature is -80 to -120°C.

[0024] During directional freezing, the cold source is located at the bottom of the mold. During the cooling process, ice crystals begin to nucleate from the cold source and grow parallel to the temperature gradient direction (away from the cold source) until the silk fibroin aqueous solution is completely frozen to form ice crystals / silk fibroin scaffolds.

[0025] As further preferred, the initial temperature is 10 to -90°C, the cooling rate is 0 to 10°C / min, and the final temperature is -80 to -90°C. As further preferred, the initial temperature is -90°C, the cooling rate is 0°C / min, and the final temperature is -90°C.

[0026] As a further preferred embodiment, the mold is a polymer mold prepared by a fused deposition modeling process. The geometric shape of the mold is a hollow cubic structure with openings at the top and bottom.

[0027] As a further preference, the cold source includes but is not limited to liquid nitrogen, dry ice, alcohol bath, etc. A further preferred cold source is an alcohol bath. The alcohol bath has a matching electronic temperature control device, which can accurately control the cooling process.

[0028] In the above step (2):

[0029] The freeze drying is carried out in a vacuum freeze dryer.

[0030] Preferably, the freeze-drying temperature is -40 to -80°C and the pressure is 1 to 600Pa.

[0031] As a further preference, the freeze-drying temperature is -70 to -80°C, and the pressure is 1 to 20 Pa. As a further preference, the freeze-drying temperature is -76°C, and the pressure is 10 Pa.

[0032] Preferably, the freeze-drying time is 2 to 48 hours, more preferably 5 to 20 hours, and even more preferably 12 hours.

[0033] In the above step (3):

[0034] Preferably, the oriented porous silk scaffold is placed in a humid environment for humidification;

[0035] The humidification humidity is 75 to 98%, and the humidification time is 0.2 to 10 hours.

[0036] As a further preference, the humidification humidity is 80% and the humidification time is 0.5 h.

[0037] As further preferred, the dehumidification temperature is 25°C.

[0038] The above-mentioned humid environment can be provided by a humidification device.

[0039] Preferably, the pressure used for mechanical compaction is 1 to 100 MPa, more preferably 1 to 50 MPa, and even more preferably 20 MPa.

[0040] Preferably, the mechanical compaction time is 1 to 120 min, more preferably 1 to 50 min, and even more preferably 20 min.

[0041] Preferably, the direction of the force applied by the mechanical pressure is perpendicular to the direction of the temperature gradient formed by the directional freezing.

[0042] The oriented porous silk scaffold is subjected to humidification and mechanical compaction treatments to increase the interfacial bonding force between the pore walls of the oriented porous silk scaffold.

[0043] The above mechanical compaction can be achieved by a tablet press.

[0044] In the above step (4):

[0045] Preferably, the polar solvent is one or more of methanol, ethanol and propanol. The purpose of polar solvent treatment is to induce the formation of β-folding.

[0046] As further preferred, the polar solvent is ethanol.

[0047] Preferably, the volume fraction of the polar solvent is 50 to 99 v / v%, more preferably 80 to 99 v / v%, and even more preferably 95 v / v%.

[0048] Preferably, the silk scaffold is immersed in the polar solvent for 4 to 48 hours, more preferably 20 to 30 hours, and even more preferably 24 hours.

[0049] After the soaking is completed, the polar solvent on the silk fibroin scaffold can be removed by washing with water. Specifically, the soaked silk fibroin scaffold can be washed three times with deionized water.

[0050] The preparation method of the unidirectional strong and tough silk fibroin scaffold of the present invention regulates the microscopic orientation structure of the silk material through a directional freezing process, and then prepares a highly oriented, highly crystalline and biodegradable strong and highly biocompatible silk fibroin scaffold through humidification, mechanical compaction and polar solvent-induced β-folding crystallization. The preparation method has the advantages of simple equipment, simple operation, rapid and batch preparation and low economic cost. The unidirectional strong and tough silk fibroin scaffold prepared by the above method can be used in tissue engineering and regenerative medicine research.

[0051] The present invention also provides a unidirectional strong and tough silk fibroin scaffold, which is prepared by any of the above-mentioned methods for preparing the unidirectional strong and tough silk fibroin scaffold.

[0052] It is worth pointing out that the materials involved in the present invention can be obtained from commercial channels unless otherwise specified.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) The method for preparing the unidirectional strong silk fibroin scaffold of the present invention has the advantages of simple equipment, simple process operation, rapid and batch preparation, suitability for industrial production and low economic cost.

[0055] (2) The method for preparing the unidirectional strong silk fibroin scaffold of the present invention does not add or involve toxic or harmful substances during the preparation process, thereby ensuring the high biocompatibility of the silk fibroin scaffold.

[0056] (3) The method for preparing a unidirectional strong and tough silk fibroin scaffold of the present invention can prepare a strong and tough silk fibroin scaffold that is highly oriented at the macroscopic and microscopic levels, has a tight interface, and has an increased β-folding content. Among them, the unidirectional silk fibroin fibers and β-folding crystals have crack pinning and crack delay effects, which improve the toughness of the silk fibroin scaffold.

[0057] (4) The unidirectional strong silk fibroin scaffold of the present invention presents a highly ordered single orientation, which is a bionics of the natural Achilles tendon structure. This orientation can not only enhance the mechanical properties, but also improve the efficiency of stress transfer.

[0058] (5) The unidirectional strong silk protein scaffold of the present invention has excellent mechanical properties, with a tensile strength of up to 5.12 MPa, and exhibits excellent fatigue resistance, excellent biocompatibility and in vivo degradability. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a schematic diagram of the preparation process of the single-oriented strong silk fibroin scaffold in Example 1;

[0060] Figure 2 In the figure, a is a front view scanning electron microscope image of the silk fibroin scaffold before mechanical compaction in Example 1, b is a front view scanning electron microscope image of the silk fibroin scaffold after mechanical compaction in Example 1; c is an infrared spectrum image of the silk fibroin scaffold prepared in Example 1;

[0061] Figure 3 In the figure, a and b are bending, folding and torsion diagrams of the single-oriented strong silk fibroin scaffold prepared in Example 1, respectively; c is a load-bearing capacity test diagram of the single-oriented strong silk fibroin scaffold prepared in Example 1;

[0062] Figure 4 This is an infrared spectrum of the single-oriented strong silk fibroin scaffold prepared in Example 2;

[0063] Figure 5 is a tensile stress-strain curve of the single-oriented strong silk fibroin scaffold prepared in Example 1;

[0064] Figure 6 This is a graph showing the results of the mechanical strength cycle test of the single-oriented strong silk protein scaffold prepared in Example 1. DETAILED DESCRIPTION

[0065] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In addition, it should be understood that after reading the contents of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0066] The water-soluble silk fibroin used in the following examples and comparative examples was purchased from Suzhou Yongqinquan Intelligent Equipment Co., Ltd., and the model number is EFL-SF-001.

[0067] Embodiment 1:

[0068] A method for preparing a unidirectional strong silk fibroin scaffold, such as Figure 1 As shown, the following steps are included:

[0069] (1) First, prepare a silk fibroin aqueous solution: using magnetic stirring, dissolve 0.4 g of water-soluble silk fibroin in 10 mL of deionized water, filter to remove insoluble silk fibroin, and then centrifuge to remove bubbles to obtain a silk fibroin aqueous solution with a concentration of 4 wt%; wherein the centrifugal speed is 1000 r / min and the centrifugal time is 5 min.

[0070] (2) Directed freezing process: Place a hollow cube structure mold with upper and lower openings on an alcohol bath with an electronic temperature control device (only the bottom is in contact with the cold source), pour the silk protein aqueous solution into the mold, set the initial temperature of the cold source to -90°C, and the cooling rate to 0°C / min. Ice crystals will begin to nucleate from the cold source and then grow parallel to the temperature gradient direction (away from the cold source) until the whole is frozen to form an ice crystal / silk scaffold.

[0071] (3) Removing ice crystals: Place the ice crystal / silk scaffold into a vacuum freeze dryer, set the freeze drying temperature to -76°C and the pressure to 10 Pa, and freeze dry the ice crystal / silk scaffold for 12 hours to obtain a silk scaffold with directional pores, in which the pores are along the freezing direction (temperature gradient direction).

[0072] (4) Humidification and mechanical compaction: The oriented porous silk scaffold was placed in a humidification device, and the humidification temperature was set to 25°C, the humidity was set to 80%, and the humidification time was set to 0.5 h;

[0073] The moistened silk scaffold was compacted using a tablet press, wherein the compaction pressure was set to 20 MPa, the pressure duration was 20 min, and the direction of mechanical pressing force was perpendicular to the direction of the temperature gradient during directional freezing; the purpose of the mechanical compaction operation was to enhance the interfacial bonding force between the pore walls of the silk scaffold.

[0074] (5) Polar solvent induced crystal transformation: The compacted silk scaffold was immersed in 95 v / v% ethanol for 24 h; the immersed silk scaffold was washed three times with deionized water to remove the residual alcohol, and finally a high-strength and high-biocompatible silk scaffold (single-oriented strong silk scaffold) was obtained. In this step, ethanol was used to induce the transformation of the α phase, random coil phase and β-turn phase in the silk fibroin into a β-fold phase with high mechanical strength.

[0075] Figure 2 Middle a is a front view SEM image of the silk scaffold after humidification without mechanical compaction. Figure 2 b is a front view scanning electron microscope image of the silk scaffold after mechanical compaction; Figure 2 It can be seen that the silk scaffold after mechanical compaction presents a single orientation in the horizontal direction.

[0076] The infrared spectrum of the high-strength, high-toughness and high-biocompatibility silk fibroin scaffold prepared in this example after being soaked in ethanol and washed with deionized water is as follows: Figure 2 As shown in c; Figure 2 As can be seen in Figure c, its infrared spectrum shows characteristic peaks of β-folded crystals, which are located at 1698 cm -1 , 1622cm -1 and 1515cm -1 , demonstrating the successful induction of the β-sheet phase.

[0077] The bending, folding and torsion diagrams and the load-bearing capacity test diagrams of the silk fibroin scaffold prepared in this embodiment are shown in FIG. Figure 3 shown by Figure 3 As can be seen from a and b, the 4 wt% silk fibroin scaffold prepared in this example exhibits excellent flexibility and can be bent and folded; Figure 3As can be seen from figure c, the silk fibroin scaffold prepared above can bear a dumbbell weighing 5 kg, and has excellent load-bearing capacity.

[0078] The mechanical properties of the silk fibroin scaffold prepared above were tested. The tensile stress-strain curve of the silk fibroin scaffold was as follows: Figure 5 As shown. Figure 5 It can be seen that the tensile mechanical strength of the silk fibroin scaffold is as high as 5.12MPa, and the elongation at break is as high as 191%. The experimental process was tested in accordance with the tensile performance test standard ASTM D638 for plastics.

[0079] The cyclic tensile test of the silk fibroin scaffold prepared above was carried out, and the results are as follows Figure 6 As shown. Figure 6 It can be seen that after multiple cycles, the silk fibroin scaffold still maintains good strength and toughness. The experimental process refers to the tensile performance test standard ASTM D638 for plastics, and the cyclic tensile strain is set to 50%.

[0080] Embodiment 2:

[0081] A method for preparing a unidirectional strong silk fibroin scaffold comprises the following steps:

[0082] (1) First, prepare a silk fibroin aqueous solution: using magnetic stirring, dissolve 2 g of water-soluble silk fibroin in 10 mL of deionized water, filter to remove insoluble silk fibroin, and then centrifuge to remove bubbles to obtain a silk fibroin aqueous solution with a concentration of 20 wt%; wherein the centrifugal speed is 1000 r / min and the centrifugal time is 5 min.

[0083] (2) The treatment was carried out according to steps (2) to (5) in Example 1, and finally a silk fibroin scaffold with high strength, toughness and biocompatibility (single-oriented strong silk fibroin scaffold) was obtained.

[0084] The infrared spectrum of the high-strength and high-biocompatibility silk fibroin scaffold prepared in this embodiment after alcohol immersion and cleaning is as follows: Figure 4 shown by Figure 4 It can be seen that its infrared spectrum shows characteristic peaks of β-folded crystals, which are located at 1698cm -1 , 1622cm -1 and 1515cm -1 , demonstrating the successful induction of the β-sheet phase.

[0085] The mechanical properties of the silk fibroin scaffold prepared in this embodiment were tested, and the tensile mechanical strength of the silk fibroin scaffold was as high as 7.8MPa, and the elongation at break was as high as 287.43%. Compared with the mechanical properties of the silk fibroin scaffold prepared in Example 1, the concentration of the silk fibroin aqueous solution used in this embodiment is 20wt%, which is too expensive; while the mechanical properties of the silk fibroin scaffold prepared by the 4wt% silk fibroin aqueous solution in Example 1 can meet the requirements of general applications. Therefore, considering comprehensive factors, the concentration of the silk fibroin aqueous solution is preferably 4wt% without special requirements.

[0086] Embodiment 3:

[0087] (1) According to step (1) of Example 1, a silk fibroin aqueous solution with a concentration of 4 wt % was prepared.

[0088] (2) Directed freezing process: Place a hollow cubic structure mold with upper and lower openings on an alcohol bath with an electronic temperature control device (only the bottom is in contact with the cold source), pour the silk protein aqueous solution into the mold, set the initial temperature of the cold source to -10°C, the cooling rate to 10°C / min, and the final temperature to -90°C to start cooling. Ice crystals will begin to nucleate from the cold source and then grow parallel to the temperature gradient direction (away from the cold source) until the whole is frozen to form an ice crystal / silk scaffold.

[0089] (3) The treatment was carried out according to steps (3) to (5) described in Example 1 to finally obtain a silk fibroin scaffold with high strength, toughness and biocompatibility.

[0090] Embodiment 4:

[0091] (1) Processing is performed according to steps (1) to (3) in Example 1 to obtain a silk fibroin scaffold with directional pores.

[0092] (2) Moisturization and mechanical compaction: Place the oriented porous silk scaffold in a moisturizing device, set the moisturizing temperature to 25°C, the humidity to 80%, and the moisturizing time to 0.5 h;

[0093] The moistened silk scaffold was compacted using a tablet press, wherein the compaction pressure was set to 50 MPa, the compaction duration was set to 20 min, and the direction of mechanical pressing force was perpendicular to the direction of the temperature gradient during directional freezing; the purpose of the mechanical compaction operation was to enhance the interfacial bonding force between the pore walls of the silk scaffold.

[0094] (3) The treatment was carried out according to step (5) in Example 1 to finally obtain a silk fibroin scaffold with high strength, toughness and biocompatibility.

[0095] Comparative Example 1: Non-directional freezing, no temperature gradient

[0096] (1) According to step (1) described in Example 1, a silk fibroin aqueous solution with a mass fraction of 4 wt% is obtained.

[0097] (2) Freezing process: Place the mold with an open top surface in a constant temperature refrigerator (cold source) with an electronic temperature control device (the temperature of each surface of the mold is the same, and there is no temperature gradient), pour the silk fibroin aqueous solution into the mold, set the initial temperature of the cold source to -90°C, and the cooling rate to 0°C / min. Freeze the silk fibroin aqueous solution until the entire solution is frozen to form ice crystals / silk fibroin scaffolds.

[0098] (3) Processing according to steps (3)-(5) described in Example 1 to obtain a disordered silk protein scaffold.

[0099] The mechanical properties of the disordered silk fibroin scaffold prepared in Comparative Example 1 were tested, and the tensile strength was 402 KPa, and the elongation at break was 13.3%, indicating poor mechanical properties.

[0100] Comparative Example 2: No humidification and mechanical compaction treatment

[0101] (1) Follow steps (1)-(3) in Example 1 to obtain a silk fibroin scaffold with oriented pores.

[0102] (2) Directly treat the silk fibroin scaffold according to step (5) in Example 1 to finally obtain a silk fibroin scaffold.

[0103] The mechanical properties of the silk fibroin scaffold prepared in Comparative Example 2 were tested, and the tensile mechanical strength was 61.43 KPa, and the elongation at break was 35%, indicating poor mechanical properties, which illustrates the positive effects of moisture treatment and mechanical compaction treatment on improving the mechanical properties of the scaffold.

[0104] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a unidirectional strong silk fibroin scaffold, characterized in that: The following steps are involved: (1) Directionally freezing the silk fibroin aqueous solution to prepare ice crystal / silk fibroin scaffolds; (2) freeze-drying the ice crystal / silk scaffold to remove the ice crystals and obtain a directional porous silk scaffold; (3) sequentially subjecting the oriented porous silk scaffold to humidification and mechanical compaction treatments; (4) Immersing the compacted silk fibroin scaffold in a polar solvent for cross-linking, and washing with water after immersion to obtain the unidirectional strong silk fibroin scaffold.

2. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: The concentration of the silk fibroin aqueous solution is 1-50 wt %.

3. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: In step (1), the specific process of directional freezing the silk fibroin aqueous solution is as follows: Placing a mold with upper and lower openings on a cold source with a temperature control device, pouring a silk fibroin aqueous solution into the mold, and controlling the cold source to cool the silk fibroin aqueous solution until the silk fibroin aqueous solution is completely frozen, thereby completing directional freezing; The initial temperature of the cold source is set to 20 to -120°C, the cooling rate is 0 to 20°C / min, and the final temperature is -80 to -120°C.

4. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: In step (2), the freeze-drying temperature is -40 to -80°C and the pressure is 1 to 600 Pa.

5. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: In step (3), the oriented porous silk scaffold is placed in a humid environment for humidification; The humidification humidity is 75 to 98%, and the humidification time is 0.2 to 10 hours.

6. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: The pressure used for mechanical compaction is 1 to 100 MPa.

7. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: The direction of the mechanical pressure is perpendicular to the direction of the temperature gradient formed by the directional freezing.

8. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: The polar solvent is one or more of methanol, ethanol and propanol.

9. The method for preparing a unidirectional strong silk fibroin scaffold according to claim 1, characterized in that: The volume fraction of the polar solvent is 50 to 99 v / v%.

10. A unidirectional strong silk fibroin scaffold, characterized in that: The unidirectional strong silk fibroin scaffold is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing silk fibroin three-dimensional porous material

    CN101905035A

  • Stent type silk fibroin film insoluble in water, and preparation and application of stent type silk fibroin film

    CN102847194A

  • Method using ice crystal template method to prepare three-dimensional biological scaffold with regular lamellar structure and application of method

    CN106039400A

  • Application of aromatic alcohol as silk fibroin inducer and treatment method of silk fibroin

    CN110903372A

  • Method for treating silk fibroin by aromatic alcohol and application of aromatic alcohol in preparation of silk-fibroin-containing materials

    CN112979779A